A multi-scale approach for pasta quality features assessment. (March 2019) - Diantom, Agoura; Curti, Elena; Carini, Eleonora; Boukid, Fatma; Mattarozzi, Monica; Vodovotz, Yael; Careri, Maria; Vittadini, Elena
Abstract: Pasta industry has introduced in the market new pasta formulations to respond to consumers' nutritional/health needs. The resulting macromolecular, mesoscopic, and microscopic changes induced in pasta need to be evaluated. In this work, a multi-scale screening of physico-chemical properties was performed on commercial pasta formulations (wheat semolina, whole wheat semolina, veggie, gluten free). Pasta samples showed significantly (p ≤ 0.05) different properties: wheat semolina and whole flour samples had a more pronounced viscoelastic behaviour (Dynamic Mechanical Analysis), higher hardness (Texture Analysis) and higher mobility of the more rigid protons ( 1 H Nuclear Magnetic Resonance); veggie pasta had the highest frozen water content and higher 1 H T2 molecular mobility; gluten free pasta showed a larger rigid population (Population C). This study indicated the ability of a multi-scale approach in discriminating pastas' formulation. Besides physico-chemical properties, 1 H NMR was particularly able to properly discriminate pastas' formulations. Highlights: A multi-scale screening of physico-chemical properties of pasta was performed. Wheat semolina, whole wheat semolina, veggie, and gluten free pasta were evaluated. Unconventional DMA and TD-NMR Relaxometry techniques were used. 1 H TD-NMR Relaxometry was a valid tool to describe pasta properties.